Low Parathyroid Hormone Versus Secondary Hyperparathyroidism and Survival in Patients Undergoing Hemodialysis: A Propensity-Matched Analysis - Guo, Wang; Zhang, Huixian; Zhang, Yamei; Huang, Hongdong; Liu, Wenhu; Diao, Zongli (Frontiers in Endocrinology, 2022)
Introduction Low serum parathyroid hormone (PTH) and secondary hyperparathyroidism (SHPT) are very common in patients undergoing hemodialysis. However, it remains unclear which of these has a lower mortality. Objective In this study, we compared outcomes between hemodialysis patients with low PTH and those with SHPT. Methods This was a multi-center, retrospective, matched cohort study. Median intact PTH (iPTH) was used as the cutoff for allocating participants to low PTH (iPTH<100 pg/mL) and SHPT groups (iPTH ≥600 pg/mL). Sex, diabetes, age, and dialysis vintage were matched between the groups. The primary outcome was all-cause death at 72 months. Results The study cohort comprised 2282 patients (1166 in each study group). Prior to matching, the primary outcome occurred in 429/1166 patients (36.79%) in the low PTH group and in 284/1116 (25.45%) in the SHPT group. There were no significant differences in all-cause death between the groups according to multivariable Cox regression (P=0.423). The hazard ratio for low PTH versus SHPT was 1.08 (95% confidence interval, 0.90–1.30). Propensity matching created 619 pairs of patients. Baseline characteristics, including age, sex, diabetes, and dialysis vintage were comparable between the groups. The primary outcome occurred in 195/619 patients (31.50%) in the low PTH group and in 193/619 (31.18%) in the SHPT group. There were no significant differences in all-cause death between the groups according to multivariable Cox regression (P=0.43). The adjusted hazard ratio for low PTH versus SHPT was 1.10 (95% confidence interval, 0.87–1.39). Conclusions Hemodialysis patients with low PTH have similar all-cause death rates to the rates for those with SHPT.